Should Contact Recreation Water Quality Standards be Consistent across Hydrological Extremes?. (7th May 2019) - Gregory, Lucas F.; Gitter, Anna; Muela, Stephen; Wagner, Kevin L.
Abstract: Water quality standards are developed to protect and define when waterbodies support their designated uses including public water supply, recreational use, aquatic life use, and others. Recreational use categories include various activities that typically do not occur under similar hydrologic conditions making protection of all uses challenging. This paper presents a case study where Escherichia coli concentrations were grouped by flow rate to demonstrate potential effects of developing use‐specific water quality standards for contact recreation. Adopting this approach requires a shift from current water quality policy which applies to all hydrologic conditions; however, it also requires additional data collection on actual usage types and occurrence before it can be implemented. This paper demonstrates that implementing an alternative water quality standards approach can still reasonably protect human health while minimizing taxpayer cost to restore impaired waterbodies.